Anticoagulation in patients with auricular fibrilation and amiloid angiopathy Review of a complex subject based on scientific literature (Boletin Médico de Postgrado, 2022)
The risk of ischemic stroke in atrial fibrillation can be quantified by the CHA2DS2-VASc score. High risk patients according to the CHA2DS2-VASC score should be anticoagulated, however cerebral amyloid angiopathy increases the risk of intracranial hemorrhage. This review aims to highlight the current management of patients with cerebral amyloid angiopathy and atrial fibrillation. Bleeding biomarkers for cerebral amyloid angiopathy include cortical microhemorrhages, cortical superficial siderosis, convex subarachnoid hemorrhage, deep intracerebral hemorrhage, and lobar hemorrhage. The scientific evidence indicates that deep intracerebral hemorrhage has an annual recurrence rate of 8,9% and for annual lobar hemorrhage it is greater than 19%. Cortical microhemorrhages increase the risk of deep and lobar intracerebral hemorrhage with the prescription of oral anticoagulants, with a dose-dependent effect. In patients with atrial fibrillation, anticoagulants should be avoided in the presence of cerebral amyloid angiopathy and predominant bleeding risk characteristics such as superficial cortical siderosis or deep intracerebral hemorrhage. A randomized controlled trial comparing oral anticoagulants with a left atrial appendage closure device would help resolve this thrombosis-bleeding dilemma in these patients.
Keywords: cerebral amyloid angiopathy; atrial fibrillation; anticoagulation; intracerebral hemorrhage; thrombosis